RETRACTED: Comparison of NO3 anion levels in fruits from different climatic regions - Shvetsova Svetlana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001